Структура полимерных композитов на основе диоксида ванадия и их диэлектрические свойства в диапазоне радиочастот - Колбунов, В.Р.; Тонкошкур, А.С.; Антонова, Е.В. (Технология и конструирование в электронной аппаратуре, 2015)
Исследованы диэлектрические свойства композитов «полиэтилен — диоксид ванадия» с объемной долей наполнителя от 10 до 30% в диапазоне радиочастот и интервале температуры 20—60°С. Показано, что наблюдаемая дисперсия диэлектрической проницаемости может быть обусловлена максвелловским разделением носителей заряда в частицах полупроводникового наполнителя. Проведенный анализ зависимости низкочастотной диэлектрической проницаемости от объемной доли наполнителя позволил установить, что исследованный композит относится к двухкомпонентным статистическим смесям с наличием переходного слоя между компонентами. Досліджено діелектричні властивості композитів «поліетилен — діоксид ванадію» з об'ємною часткою наповнювача від 10 до 30% в діапазоні радіочастот та інтервалі температури 20—60°С. Показано, що спостерігається дисперсія діелектричної проникності, що може бути обумовлено максвелловським розділенням носіїв заряду в частинках напівпровідникового наповнювача. Проведений аналіз залежності низькочастотної діелектричної проникності від об'ємної частки наповнювача дозволив встановити, що досліджений композит належить до двокомпонентних статистичних сумішей з наявністю перехідного шару між компонентами. Polymer composites with active fillers are recently considered to be promising materials for the design of new functional devices with controllable properties and are intensively investigated. Dielectric studies are one of the most effective methods for studying structural features and mechanisms of conductivity formation for this type of two-component systems. The paper presents research results of the dielectric characteristics in the range of radio frequency of 50 kHz — 10 MHz and temperature range of 30—60°C of polyethylene composites of vanadium dioxide with different volume fractions of filler. Two dispersion areas were found: a high-frequency area caused by the Maxwell charge separation on the boundaries of the polyethylene matrix — conductive filler of VI2 crystallites, and a low frequency area associated with the presence of the transition layer at this boundary. The relative permittivity of the composite has a tendency to a decrease in absolute value with increasing temperature. The analysis of the low-frequency dependence of the dielectric constant of the value of the filler’s volume fraction revealed that the investigated composite belongs to two-component statistical mixtures with a transition layer between the components.